Recurrent discrete transformation in monitoring of extended signals - Швець, В. А. (Proceedings of National Aviation University (archive), 2000)
Described is Fourier algorithm of recurrent conversion providing increased resolution, absence of false petals, possibility of spectral analysis of signals of very large duration. The algorithms can have a broad band of applications in radiolocation, hydrolocation, synthesis of speech and music, image and seismogramme processing and many other areas